Computational Fluid Dynamics : An Introduction to Modeling and Applications - Khalil, Imane; Lakkis, Issam (McGraw-Hill's AccessEngineeringLibrary., 2023)
This book is not a traditional computational fluid dynamics (CFD) textbook. While current CFD books explain and derive the numerical methods used to solve fluid dynamics problems, programming these methods on computers is a tedious process for undergraduate engineering students who are primarily interested in using com-putational modeling software to solve engineering problems without "re-inventing the wheel.